Tiras da Mafalda : um estudo enunciativo da categoria de pessoa - Farina, Luciane Schiffl (2010)
The present work is an enunciative study of texts of the discursive gender comic strip and aims to demonstrate the construction of the category of person, according to the Theory of Enunciation by Émile Benveniste. According to this author, the enunciation is a unique and unrepeatable fact. It is characterized by the presence of an I (announcer), who by appropriating the language and stating, introduces the you (addressee) - condition that is reversible in a given time and space. Together, these elements (categories of person, time and space) make up the structure of the enunciation. Benveniste proposes subjectivity in language as a property held for the category of person. To do so, Mafalda s strips were used as corpus for the analyses. Despite finding in the formal structure of the strip the iconographic language, in this study it is recognized as a complement to verbal language, in a linguistic-textual perspective. This happens because the research takes the enunciative perspective in such a way that the principles of the Theory of Enunciation according to Benveniste are used to study the word in a discursive context. The conclusion of this study is that from Mafalda´s verbal manifestations, linguistic marks betray the category of person, through the constitution of an I-child and an I-adult in and within the enunciation, which directs the discursive meaning of the strip